Study of the Distribution of Gastropods in Coastal Conservation Area Pariaman City Province West Sumatera - Deddy Bahagia Manik; Afrizal Tanjung; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Coastal waters Pariaman conservation area is one of the coastal areas inhabited by other marine organisms, one of which is a gastropod. This area also did turtle breeding. The research was conducted in May 2013 in the coastal town conservation area west Sumatran province pariaman. The study is titled study of the distribution of gastropods in coastal conservation area pariaman city. The method used in this study is a survey method.The purpose of this study was to determine the distribution of gastropods. Based on the results of this research found that 13 species of gastropods, Cerithidea quadrata, Drupa morum, Littrorina undulate, Marmarostoma joblensis, Marmarostoma ticaonicus, Lineate Natica, Nerita costata, Nerita undata, Planaxis sulcatus, Terebralia sulcata, Torinia variegate, Turbo Chrysostom, Vasum ceramicum. In this study, the results obtained are clustered spreading, this is because Id> 1.Keyword: Gastropod, Distribution, Pariaman City